Conceptual generalisation in fear conditioning using single and multiple category exemplars as conditional stimuli – electrodermal responses and valence evaluations generalise to the broader category. Issue 4 (19th May 2022) - Patterson, Rachel R.; Lipp, Ottmar V.; Luck, Camilla C.
ABSTRACT: Conceptual generalisation occurs when conditional responses generalise to novel stimuli from the same category. Past research demonstrates that physiological fear responses generalise across categories, however, conceptual generalisation of stimulus valence evaluations during fear conditioning has not been examined. We investigated whether conceptual generalisation, as indexed by electrodermal responses and stimulus evaluations, would occur, and differ after training with single or multiple conditional stimuli (CSs). Stimuli from two of four categories (vegetables, farm animals, clothing, and office supplies) were used as the CS+ (followed by an electric stimulus) or CS- (presented alone). Generalisation was assessed by presenting novel stimuli from the CS categories after acquisition, extinction, and reinstatement. One category exemplar was used as the CS+ and CS- in the single group, whereas three exemplars were used as the CS+ and CS- in the multiple group. Electrodermal responses generalised in acquisition and extinction but did not differ between groups. In the multiple group, CS evaluations generalised in acquisition and extinction, whereas generalisation was not evident in the single group. Training with multiple CSs also resulted in the extinction of stimulus valence. The current findings have implications for future research examining the generalisation of valence and for exposure-based treatments of anxiety.